1897 Iowa Code Ann. 1955 - (:unkn) unknown (My University, 1897)
§ 5004: Prohibited selling, presenting, or giving, any pistol, revolver, or toy pistol to any minor. Violators fined not less than twenty-five nor more than one hundred dollars, or imprisoned not less than ten nor more than thirty days in jail.
Keywords: TRANSFER - MINORS